LO010: Clinical assessment of transient ischemic attack patients for symptomatic carotid disease in the emergency department. (2nd June 2016) - Motamedi, N.; Abdulaziz, K.; Sharma, M.; Perry, J.J.
Abstract : Introduction: TIAs precede about 30% of strokes, with 4-10% having a stroke within 90 days of their TIA. In patients with a TIA due to symptomatic carotid disease, diagnosis and treatment within 2 weeks has been shown to have much better outcomes, while delay beyond 12 weeks no longer reduces subsequent stroke risk. The objective of this study was to determine the clinical findings associated with symptomatic critical disease following an ED visit for TIA to indicate patients requiring prompt carotid imaging.Methods: We performed a prospective Canadian multicenter cohort study, at 13 academic sites, of ED patients with TIA or non-disabling stroke from 2006-2014. Treating ED physicians indicate clinical features on standardized data collection forms. Symptomatic carotid disease was carotid stenosis 50-99%, or carotid dissection, adjudicated by stroke neurology to be the etiology of the index event. Patients were followed by medical review and telephone up to 90 days. Univariate analysis was conducted for clinical features associated with patients who were eventually found to have symptomatic carotid disease as a cause for their TIA.Results: The cohort included 305 patients with and 5, 277 without symptomatic carotid disease. Positive predictors of symptomatic carotid disease included older age (74.0 yrs vs 68.0 yrs p<0.0001), male sex (62.9% vs 47.9%; p<0.0001), history of weakness (63.3% vs 41.4%; p<0.0001), language disturbance (52.1% vs 40.0%; p<0.0001), weakness on physical exam (25.5% vs 17.1%; p=0.0002), history of hypertension (74.8% vs 59.5%; p<0.0001), and known history of carotid stenosis (18.9% vs 3.1%; p<0.0001). Negative predictors of symptomatic carotid disease included first ever TIA (56.8% vs 68.8%; p<0.0001), history of altered sensation (39.4% vs 45.8%; p=0.0322), lightheadedness (13.0% vs 22.4%; p=0.0002), and vertigo (3.6% vs 12.7%; p<0.0001).Conclusion: TIA patients with older age, male sex, weakness, language disturbance or history of carotid stenosis need to be promptly imaged to assess for symptomatic carotid disease.